Soil Fumigation after Methyl Bromide: Managing Concentrations of Drip-Applied Metam Potassium for Nutsedge Control - Bielinski M. Santos; James P. Gilreath (EDIS)
This 2-page fact sheet presents the results of studies conducted to determine the influence of metam potassium concentrations on purple nutsedge control. Written by Bielinski M. Santos and James P. Gilreath, and published by the UF Department of Horticultural Sciences, April 2012.